The impact of debt finance on the financial performance of a firm: a case of City of Mutare - Ruguwa, Charles K. (Midlands State University, 2018)
The purpose of this study was to determine the impact of debt finance on financial performance of a firm using City of Mutare as a case. City of Mutare adopted debt financing in order to enhance their financial performance but their trend analysis illustrated a decline in profit margins at an average rate of 45.03% per annum since 2014, this motivated the researcher to carry out this study.The study employed a mixed approach in carrying out the study which include both quantitative and qualitative approach. The research data was gathered from questionnaires and interviews, with questionnaires yielding a response rate of 84.21%, whilst there was 100% response rate for interviews. The statistical packages used for regression analysis were Excel and Stata 14.2 and the independentvariables were long term debt, short term debt, total debt and tangibility and ROA was the dependent variable in the study. The major research findings from the information obtained were that City of Mutare adopted a poor debt financing and it is not effectively maintained resulting in poor financial performance and also the study found out that there are other benefits of debt financing which can enhance financial performance given that debt is effectively maintained and kept at an optimal debt ratio. The researcher concluded this study by recommending City of Mutare management to reduce their debt financing and rely more on internal funds because they are cheap and easy to maintain and they do not result in external contractual obligations. Lastly, the researcher stated that the company should utilize debt as the last resort and should be kept at a low and optimal level in order to maximize profits.